EVALUATION OF EFFECTIVENESSES OF ELEMENTS OF PROMOTION STRATEGY ON SALES VOLUME IN DJAGUNG PRIMA CIGARETTE COMPANY MALANG - Putra, Angga Hutama; yo, Sunar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aims to evaluate the effectiveness of sales promotion tools to support sales volume in PR Djagung Prima Malang. Konglomorov-Smirnoff test, Single Sample T-test, Wilconson Sign Rank test and Friedman test conducted to acknowledge the relationships among each promotion tools (Advertising, Personal Selling and Sales Promotion) of PR Djagung Prima. All facets of each elements of promotional strategyalso wereevaluated to understand the most effective promotion strategy among all. This study is explanatory research, in accordance with its purpose to describe the causal relationship among variables through hypothesis testing. The samples and populationof this study were the customers of PR Djagung Prima Malang. In this study,the data collection method by distributing questionaire.The sampling technique used is purposive sampling and the research instruments were tested using the validity test and reliability test. The hypothesis testing used the Single Sample T-test, Wilconson Sign Rank test and Friedman test. Single sample T-test used to analyze advertising and Wilconson Sign Rank test used to analyze personal selling and sales promotion. The single sample T-test shown that all of advertising facets are effective.Wilconson Sign Rank test also shown that all facets of personal selling and sales promotion are effective. The Friedman test shown that there is no significant different between each promotion tools and its shown that nameplate in the store is the most effective promotion tools followed simultaneously by special pricing program, nameplate in the company, salesman approach the agent and shop, salesman did presentation of their product, banner, brocure, given discount price and newspaper ads. Keywords: Promotion tools, Advertising, Personal Selling, Sales Promotion.